The Impact Of Digital Technology In The Entrepreneur Transition During The Covid-19 Pandemic - Tasmilah Tasmilah Tasmilah; Devanto Pratomo; Wildan Syafitri (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2022)
The Covid-19 pandemic has decreased the number of entrepreneurs assisted by permanent workers in Indonesia. Using SAKERNAS Data of August 2019 and 2020, this study uses multinomial logistic regression to estimate the impact of digital technology in the entrepreneurial transition during the Covid-19 pandemic. The results show that digital technology and the internet have a negative and significant effect on the transition of formal entrepreneurship in Indonesia. The use of digital technology and the internet will prevent formal entrepreneurs from transitioning into informal entrepreneurs or leaving entrepreneurship. Increasing digital technology usage and the internet for promotional and sales purposes will enable entrepreneurs to survive amid a pandemic. In addition, building information technology infrastructure such as Base Transceiver Station (BTS), especially in rural areas, is necessary to increase internet coverage and encourage business scale-up in rural areas.